2023
DOI: 10.3329/jasbs.v48i1-2.64517
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pant characteristics and physiological performance of mungbean (Vigna radiata (L.) Wilczek) genotypes under salt stress

Abstract: Mungbean is a delicious popular pulse crop whose yield is hampered by biotic and abiotic factors. Salinity is considered serious abiotic stress that hinders growth and yield drastically. To find out the response features of salinity tolerance in mungbean, a series of experiments were carried out in the Department of Crop Botany of BSMRAU. The experiment was performed in the greenhouse of the Crop Botany department using nutrient solution under hydroponics conditions. Initially, fifty-two mungbean genotypes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…In our study, we found a strong diurnal activity in both areas, with a difference in the peak of activity: morning in HWS and afternoon in RYER. This strong diurnal activity and this pattern cannot be directly related to human presence in the study area, although some illegal hunting for consumption has been documented [73]. A tentative explanation on why this cathemeral species was detected mostly during the day in our study areas was that often the same camera captured both Asiatic golden cat (during day) and clouded leopard (during night) suggesting a possible competition between two medium-sized felids with similar prey [74].…”
Section: Daily Activity Patternsmentioning
confidence: 67%
“…In our study, we found a strong diurnal activity in both areas, with a difference in the peak of activity: morning in HWS and afternoon in RYER. This strong diurnal activity and this pattern cannot be directly related to human presence in the study area, although some illegal hunting for consumption has been documented [73]. A tentative explanation on why this cathemeral species was detected mostly during the day in our study areas was that often the same camera captured both Asiatic golden cat (during day) and clouded leopard (during night) suggesting a possible competition between two medium-sized felids with similar prey [74].…”
Section: Daily Activity Patternsmentioning
confidence: 67%